Multiple spatial frames for immersive working memory - Draschkow, D; Nobre, AC; Van Ede, F (Springer Nature, 2022)
As we move around, relevant information that disappears from sight can still be held in working memory to serve upcoming behaviour. How we maintain and select visual information as we move through the environment remains poorly understood because most laboratory tasks of working memory rely on removing visual material while participants remain still. We used virtual reality to study visual working memory following self-movement in immersive environments. Directional biases in gaze revealed the recruitment of more than one spatial frame for maintaining and selecting memoranda following self-movement. The findings bring the important realization that multiple spatial frames support working memory in natural behaviour. The results also illustrate how virtual reality can be a critical experimental tool to characterize this core memory system.